Plan de exportación de arándanos azules de Colombia a Estados Unidos (2021)
The purpose of this work is to explain the export of blueberries to the United States, in this work you will be able to observe the opportunities, the procedures and the different steps that must be taken to achieve the successful export of blueberries. All this to take advantage of the great opportunity that this product has in the US market, due to the high consumption of blueberries in this country for its health benefits, it is intended to take advantage of the advantages that Colombia has with the United States, for means of the FTA that has been signed since May 15, 2012.